Profitability of a value-based healthcare project for a healthcare supplier - Kolehmainen, Janette (fi=Turun yliopisto|en=University of Turku|, 2018)
This study is conducted as a qualitative case study concerning value-based healthcare and its profitability for a healthcare supplier. As a company for this study has been chosen a healthcare supplier Company X which operates in the medical technology industry. Currently, the healthcare industry confronts challenges, such as the aging population and pressure to become more cost-effective, which raises a question of alternative solutions to face and cope with them. For that reason, Michael E. Porter has proposed a concept of value-based healthcare which is based on outcome measuring, patient-evaluated experiences, freedom of choice and positive-sum competition. Value-based healthcare has gained great attention also at Company X. Due to this matter, the purpose of this study is to determine how the profitability of a value-based healthcare project can be demonstrated for a healthcare supplier Company X and how the profitability models for the value-based healthcare projects differ from the traditional fee-for-patient model. As a research approach has been selected the action-oriented approach including some features of the constructive approach. Two experts at the case company were interviewed utilizing the thematic interview method. Based on these interviews were developed two complementing profitability models for the value-based healthcare projects in Excel, which grounds for the principles of the time value of money and investment calculations. Additionally, a contribution margin based profitability model for the fee-for-patient business model was established in Excel to fulfill the comparison needs between the two business approaches. The results of this study indicated that the value-based healthcare models would be profitable for the case company. Compared to the traditional model, the value-based approach generates weaker yearly profits. However, directly comparing solely the bottoms lines of the two models do not provide a full picture of the potential business-wise opportunities and profitability. The numeric data presented in the value-based profitability models is difficult to forecast due to the contingency on the produced value for the patients, because Company X has no previous experience of the value-based projects in the Finnish subsidiary yet. However, the Finnish subsidiary has the support from the parent company and from the other subsidiaries as well as the information gained from the projects executed abroad. The value-based healthcare projects may entail a great potential for success, but solely if the real value capturing for patient populations can be truly indicated in the future.